2022
DOI: 10.3389/fphar.2022.1035895
|View full text |Cite
|
Sign up to set email alerts
|

Treatments to post-stroke depression, which is more effective to HAMD improvement? A network meta-analysis

Abstract: Introduction: Post-stroke depression (PSD) is a common mental health problem after cerebrovascular accidents. There are several treatments that have been shown to be effective in treating post-stroke depression. However, it is not clear which treatment is more effective.Methods: In this meta-analysis, an appropriate search strategy was used to search eligible randomized controlled trials (RCTs) on different treatments to treat patients with Post-stroke depression published up to December 2021 from the CNKI, Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Early use of SSRIs such as escitalopram may be a treatment for PSD (98,99). Zhang et al (100) retrieved Meta-analyzes up to December 2021. They found that antidepressant co-adjuvant therapy may enhance the efficacy of antidepressant medications, with acupuncture combined with fluoxetine being more efficacious in treating PSD at week 4.…”
Section: Ssrismentioning
confidence: 99%
“…Early use of SSRIs such as escitalopram may be a treatment for PSD (98,99). Zhang et al (100) retrieved Meta-analyzes up to December 2021. They found that antidepressant co-adjuvant therapy may enhance the efficacy of antidepressant medications, with acupuncture combined with fluoxetine being more efficacious in treating PSD at week 4.…”
Section: Ssrismentioning
confidence: 99%
“…Liang and colleagues provided a further conclusion that rTMS (≤10 Hz) combined with antidepressants tends to be more effective than antidepressants alone in patients with PSD 16 . Bayesian network meta‐analyses (NMA) suggested that rTMS combined with paroxetine may be more effective than other treatments for PSD at the end of the eighth week 10 . Additionally, several studies have found that rTMS over the left dorsolateral prefrontal cortex (DLPFC) can improve cognition in patients with dementia or vascular cognitive impairment, with or without depression 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…These nonpharmacological approaches may offer an alternative avenue for PSD treatment. [8][9][10][11][12][13] NIBS therapy is a promising measure for PSD treatment that has attracted increasing attention in recent years. The two most commonly used NIBS techniques are repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations